Impact of bank-specific characteristics, macroeconomic factors and governance Islamic and conventional bank revenue efficiencies - Kamarudin, Fakarudin (2015)
The main objective of Islamic and conventional banks is to maximize shareholders’value or wealth via profit maximization even though they are operate under two different principles. The profitability of banks is generally related to the level of bank’s profit efficiency. To attain a higher level of profit efficiency, banks should maximize their revenue efficiency rather than just focus on the cost efficiency level.Generally, bank governance plays a main role in ensuring that a bank’s efficiency is at the optimal level. Nevertheless, prior results are inconclusive. One of the mechanisms that could significantly improve the efficiency level of banks is through country governance. Few studies have examined the effect of country governance on banks revenue efficiency. In general, country governance is defined as the set of traditions and institutions by which the authority in a country is exercised. The levels of the revenue efficiency in the Islamic and conventional banks are measured using the Data Envelopment Analysis (DEA) method via the intermediation approach. Then, the potential determinants and the effect of country governance on the revenue efficiency of both banks are investigated by adopting the Multivariate Panel Regression Analysis (MPRA) via the pooled Ordinary Least Square (OLS), Fixed Effect Model (FEM), Random Effect Model (REM) and the Generalized Method of Moments (GMM) as estimation methods. The data for this study consists of 454 banks (112 Islamic and 342 conventional banks) selected from the three regions of the main hubs of Islamic banking (Middle East, Southeast Asia,and South Asia) that cover 19 countries from the year 2003 to 2011. Overall, the empirical findings suggest that the Islamic banks’ revenue efficiency level is higher than that of conventional banks’. Furthermore, this study finds that, bank size has a positive impact on both types of banks’ revenue efficiency. However,others factors, such as, capitalization and market power reveal the opposite relationship. The credit risk, liquidity and economic growth have a positive impact on the Islamic banks’ revenue efficiency. Meanwhile, inflation and market concentration have a positive impact on the conventional banks’ revenue efficiency,whilst global financial crisis and overhead expenses report the contrary findings. Finally, this study also finds that, in general, country governance dimensions, such as, voice and accountability have a positive influence on both Islamic and conventional banks’ revenue efficiency. However, the opposite effects are observed for other country governance dimensions, such as, political stability and absence of violence and control of corruption. In addition, the government effectiveness,regulatory quality and rule of law dimensions negatively influence banks’ revenue efficiency but is only significant for conventional banks. This study concludes that the levels of revenue efficiency in the Islamic and conventional banks are not just influenced by bank-specific characteristics and macroeconomic conditions, but they are also influenced by the effect of country governance.